Comorbidity as a factor of prognosis in patients with locoregionally advanced, inoperable squamocellular head and neck cancers - Kreačić, Miroslav; Ursulović, Tamara; Gavrilović, Dušica (Vojnosanitetski pregled, 2021)
Background/Aim. Patients (pts) with tumors often have other diseases or conditions in addition to their index cancer which are generally referred to as comorbidities. Due to the fact that well known risk factors for development of squamocellular head and neck cancers (HNSCC) such as tobacco and alcohol abuse can also damage other important organs, pts with this type of cancer are suitable for analyzing the influence of comorbid conditions on prognosis of the disease. The aim of our work was to assess the prevalence of comorbidities, most frequent conditions and their prognostic impact on overall survival in this particular population. Methods. Between July 2002 and January 2007 in the Institute for Oncology and Radiology of Serbia, 100 pts with locoregionally advanced, inoperable HNSCC were initially treated with neoadjuvant chemotherapy regimen, cytarabine-5 fluorouracil-cisplatinum. Median age of pts was 55 years, most of them (91%) were males with median number of applied chemo cycles being 4. Data on comorbidities were collected in prospective manner from various sources prior to the treatment. For grading of the severity of comorbid conditions, the Adult Comorbidity Evaluation 27 (ACE-27) comorbidity index was used with four degree scale (0–3). The average follow-up of pts was 15 months with range from 3–59 months. Results. Comorbidities were present in 69 (69%) pts, and 31 (39%) pts had no comorbidities prior to the treatment. Among pts with comorbid conditions prevailed alcoholics, active and former (71%), pts with chronic lung diseases (25%) and cardiovascular diseases (18%). Overall comorbidity score was defined according to the highest ranked single ailment, except in the case where two or more grade 2 ailments occured in different organ systems in which case the overall comorbidity score was designated as grade 3. Median overall survival for the whole group was 12 months. Median ACE-27 score was grade 1 (range 0–3) which was observed in 43 (43%) pts. Pts without comorbidities survived significantly longer than those with any kind of comorbidity (p = 0.0089), and the same was observed comparing survival of pts without comorbidities and those with comorbidity index 2 and 3 taken together (p = 0.0047). Results of other intergroup comparisons were of no statistic significance. Conclusion. Comorbidity is important prognostic variable in patients with locoregionally advanced HNSCC and should be properly assessed prior to therapy.